2022
DOI: 10.59331/jasd.v5i1.283
|View full text |Cite
|
Sign up to set email alerts
|

The Trend in Fertilizer Consumption and Its Impact on Crop Outputs in Nigeria

Abstract: The study analyzed the consumption trend of fertilizers (nitrogen, phosphorus, potassium and total/composite fertilizers) and examined its relationships with selected crop outputs from 1962 to 2019 in Nigeria. Time-series data were used and were sourced from the World Bank and Food and Agriculture Organization. The descriptive statistics, correlation analysis and Cobb Douglas production function were applied to analyze the data collected. The results revealed that fertilizer consumption over time exhibited a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Furthermore, the research indicated regional disparities in environmental risk indexes for phosphorus and potash, offering insights into the environmental implications of fertilizer use. Akpan et al (2022) focused on Nigeria, analyzing the consumption trend of fertilizers and its relationship with crop outputs. The study revealed significant volatility in fertilizer consumption, with the average consumption rate for composite fertilizer falling far below recommended levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the research indicated regional disparities in environmental risk indexes for phosphorus and potash, offering insights into the environmental implications of fertilizer use. Akpan et al (2022) focused on Nigeria, analyzing the consumption trend of fertilizers and its relationship with crop outputs. The study revealed significant volatility in fertilizer consumption, with the average consumption rate for composite fertilizer falling far below recommended levels.…”
Section: Literature Reviewmentioning
confidence: 99%